Population dynamics of migrant wheat aphids in China’s main wheat production region and their interactions with bacterial symbionts - Li, Tong; Yang, Gongqiang; Li, Qian; Jiang, Yueli; Kang, Dongmei; Fan, Zhiye; Gong, Zhongjun; Lu, Ruijie; Zhou, Guotao; Wu, Yuqing; Lu, Chuantao (Frontiers in Plant Science, 2023)
Sitobion miscanthi, Rhopalosiphum padi, and Schizaphis graminum are the three main pests in Chinese wheat-producing regions. In 2020, they are classified into Chinese Class-I list of agricultural diseases and pests, due to their severe harm to wheat plantings. S. miscanthi, R. padi, and S. graminum are migrant pests, understanding their migration patterns and simulating their migration trajectories would improve their forecasting and control techniques. In the last a few decades, suction-traps are widely used to monitor the movement of small insects, like aphids. In this study, we employed suction-trap to uncover the migration patterns of the three wheat aphid species in Yuanyang County, Henan Province, during 2018 to 2020. The results showed that population dynamics of migrant wheat aphids was varied. Most of the trapped samples were identified to be R. padi, and least S. graminum were collected. Typically, R. padi had two migration peaks in the three years, whereas S. miscanthi and S. graminum only exhibited one migration peak in 2018 and 2019. Furthermore, we simulated the migration trajectories of S. miscanthi and R. padi using the NOAA HYSPLIT model. The results revealed that the aphid migration trajectories varied over the years. Generally, the aphids originated from the south and migrated to the north. The infections of three aphid main facultative bacterial symbionts, Serratia symbiotica, Hamiltonella defensa, Regiella insercticola were detected in S. miscanthi and R. padi with specific PCR. Rickettsiella, Arsenophonus, Rickettsia and Wolbachia were further identified with the 16S rRNA amplicon sequencing. Biomarker searching indicated that Arsenophonus was significantly enriched in R. padi. Furthermore, the diversity analyses showed that the bacterial community of R. padi had higher richness and evenness than that of S. miscanthi. In conclusion, this study expands our knowledge about the migration patterns of aphids in the main wheat plant region of China, and reveals the interactions between bacterial symbionts and migrant aphids.